Kondisi-kondisi, Kebutuhan Serta Pemenuhan Kebutuhan Dewasa Madya - Avria Damayani; Faliha Zahra Damanik; Muhammad Alwi Rahman; Shoppyah Chairanie Simanjuntak (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Middle adulthood is a critical stage in life characterized by significant transformations in physical, psychological, and social aspects. During this period, individuals often face a decline in certain physical and mental capacities while also having opportunities to achieve greater levels of maturity. Challenges such as health issues, changing social roles, and increasing family responsibilities are commonly encountered. The complexity of fulfilling physical, emotional, and social needs increases, significantly impacting overall well-being. Addressing these needs involves various efforts, including maintaining good health, managing stress, and fostering meaningful social connections. Support from the surrounding environment plays a crucial role in helping individuals meet these needs. Therefore, a deep understanding of the challenges faced during middle adulthood is essential for improving their quality of life. The ability to manage physical and psychological changes while sustaining positive social relationships is key to achieving a balanced and fulfilling life during this phase.